Supplemental summary of cutoff rigidities calculated using the International Geomagnetic Reference Field for various epochs - Shea, M. A., 1937-; Smart, D. F., 1935-; U.S. Air Force Geophysics Laboratory (Hanscom AFB, Massachusetts : Air Force Geophysics Laboratories, Air Force Systems Command, United States Air Force, 1982)
Tables of cosmic-ray cutoff rigidities using the trajectory-tracing technique are given for three epochs of the geomagnetic field. These values have been determined utilizing the International Geomagnetic Reference Field with time derivatives applied so that the coefficients for the field model are appropriate for the following epochs: 1965.0, 1970.0, and 1975.0. Each table includes the geographic coordinates and L value of each location together with the main cutoff rigidity, the Stormer cutoff rigidity, and the effective cutoff rigidity. The altitude for which each set of values was calculated is also given. Tables for both vertical and non-vertical directions are included. These cutoff rigidity values are supplemental to those published in previous AFGL reports. In addition, minor corrections to previously published values are also included.
Research supported by the Air Force Geophysics Laboratory, Air Force Systems Command, United States Air Force, Hanscom AFB, Massachusetts.
Space Physics Division Project 2311.
ADA126266 (from http://www.dtic.mil0.
"1 November 1982."
Includes bibliographical references (page 61).
Mode of access: Internet.
Keywords: Magnetic fields; Geomagnetism; Cosmic rays; Cosmic magnetic fields; Magnetic fields; Geomagnetism; Cosmic magnetic fields; Cosmic rays -- Tables; Tables